2015
DOI: 10.1177/0145445515583247
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Parent-Produced Video Self-Modeling to Improve Independence in an Adolescent With Intellectual Developmental Disorder and an Autism Spectrum Disorder

Abstract: We evaluated a parent-created video self-modeling (VSM) intervention to improve independence in an adolescent diagnosed with Intellectual Developmental Disorder (IDD) and Autism Spectrum Disorder (ASD). In a multiple baseline design across routines, a parent and her 17-year-old daughter created self-modeling videos of three targeted routines needed for independence in the community. The parent used a tablet device with a mobile app called "VideoTote" to produce videos of the daughter performing the targeted ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 17 publications
(18 reference statements)
0
41
0
Order By: Relevance
“…People with ID are currently using several types of technological solutions, including tablets (Allen et al, 2015;Burckley et al, 2015), smartphones , portable digital players like the iPod Touch (Wu et al, 2016) or other similar devices (Mechling & Seid, 2011), desktop and laptop computers (Davies et al, 2002;Sigafoos et al, 2005), as well as telehealth cameras (Taber-Doughty et al, 2010). Optimal use of many ICT require an Internet connection.…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…People with ID are currently using several types of technological solutions, including tablets (Allen et al, 2015;Burckley et al, 2015), smartphones , portable digital players like the iPod Touch (Wu et al, 2016) or other similar devices (Mechling & Seid, 2011), desktop and laptop computers (Davies et al, 2002;Sigafoos et al, 2005), as well as telehealth cameras (Taber-Doughty et al, 2010). Optimal use of many ICT require an Internet connection.…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…Interventionists or treatment providers who are well versed in the use of systematic instruction procedures including modeling, prompting, corrective feedback, and contingent reinforcement are more likely to be successful in implementing video instruction with individuals with ASD. However, recent research (Allen et al 2015) showed that parents can effectively use video instruction to increase functional life skills of an adolescent with ASD and ID.…”
Section: Qualifications Of Treatment Providersmentioning
confidence: 99%
“…Of the 16 studies in this category, 15 studies had participants with mild to moderate IDD and only one study had participants with moderate to severe IDD. Types of intervention included: (a) VM, VM + photos, VM + VP, and VP (Allen et al, 2015;Cannella-Malone et al, 2006;Edrisinha, O'Reilly, Choi, Sigafoos & Lancioni, 2011;Horn et al, 2008;Mechling, Gast & Fields, 2008;Mechling & Gustafson, 2009;Mechling & O'Brien, 2010;Mechling & Seid, 2011;Taber-Doughty, Miller, Shurr, & Wiles, 2013;Taber-Doughty et al, 2011;Van Laarhoven & Van Laarhoven-Myers, 2006); (b) augmented feedback implemented on a computer screen (Applegate et al, 2008); (c) progressive time delay (PTD) for self-instruction using videos on an iPad (Smith et al, 2016) or using a DVD on an iPad (Hammond, Whatley, Ayres & Gast, 2010); (d) auditory cues (Alberto, Sharpton, Briggs & Stright, 1986;Taber-Doughty, 2005) with or without visual cues (Bouck et al, 2012); (e) video recording and still photographs (Mechling, Gast & Seid, 2010); and (f) GPS based software with embedded pictures (Davies et al, 2010). Studies reported gains in acquiring skills with or without support for generalisation.…”
Section: Technology-based Functional Trainingmentioning
confidence: 99%
“…The outcome measure most frequently used across this collection of intervention studies were ratings of targeted task performance such as the number of task steps completed without assistance (e.g., Allen et al, 2015;Applegate et al, 2008;Cannella-Malone et al, 2006;Edrisinha et al, 2011;Horn et al, 2008;Smith et al, 2016;Taylor et al, 2002;Van Laarhoven & Van Laarhoven-Myers, 2006). Some studies further examined whether the correct response was obtained and identified the level of assistance provided to the participant to complete the observed task (Smith et al, 2016;Taylor et al, 2002;Van Laarhoven & Van Laarhoven-Myers, 2006).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation